No Difference in Antibody Responses to Tetanus Vaccine Among HIV-Exposed and -Unexposed Infants in Botswana. (4th October 2017) - Smith, Christiana; Moraka, Natasha; Ibrahim, Maryanne; Moyo, Sikhulile; Mayondi, Gloria; Kammerer, Betsy; Leidner, Jean; Gaseitsiwe, Simani; Lockman, Shahin; Weinberg, Adriana
Abstract: Background: In Botswana, more than 10% of HIV-exposed, uninfected infants (HEU) are hospitalized or die in the first 6 months of life, largely due to infectious causes. Vaccine responses can act as a marker of the immune response to infectious antigens. Previous studies of antibody responses to vaccines in HEU have had conflicting results. We compared antibody titers to tetanus vaccine between HEU and HIV-unexposed infants (HUU), and explored whether tetanus antibody titers predicted risk of hospitalization in the first 2 years of life among HEU. Methods: 443 HIV-infected and 451 HIV-uninfected mothers and their 453 HEU / 457 HUU live-born infants were followed in a prospective observational study in Botswana ("Tshipidi"). Quantitative tetanus toxoid IgG was measured in plasma samples from 18-month-old infants. Geometric mean antibody titers (GMT) were compared between HEU and HUU infants, and between HEU infants who were or were not hospitalized by age 2. Results: Plasma was available at 18 months for 39 HEU and 42 HUU infants. Within this subset, there were 15 hospitalizations (12 in HEU) [RR of hospitalization among HEU = 1.34 ( P = 0.009)]. 73% of hospitalizations overall, and 83% in HEU, were due to infection (primarily pneumonia/bronchiolitis and gastroenteritis). Among infants who had received 3 or 4 doses of tetanus vaccine by 18 months, there were no significant differences in tetanus GMT between HEU and HUU (Fig A). Among HEU who had received 3 or 4 doses of tetanus vaccine by 18 months, there were no significant differences in tetanus GMT between infants who were hospitalized and infants who were not (Fig B). Conclusion: In this small sample of infants from Botswana, we did not identify differences in antibody responses to tetanus vaccine between HEU and HUU. Although HEU demonstrated an increased risk of hospitalization, response to tetanus vaccine did not appear to be a significant predictor of morbidity. It is possible that cell-mediated immune defects play a larger role than humoral immune defects in the increased susceptibility to infection among HEU. Disclosures: All authors: No reported disclosures.